2019
DOI: 10.1155/2019/5806321
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional TRPV1 Ion Channels in Physiology and Pathology with Focus on the Brain, Vasculature, and Some Visceral Systems

Abstract: TRPV1 has been originally cloned as the heat and capsaicin receptor implicated in acute pain signalling, while further research has shifted the focus to its importance in chronic pain caused by inflammation and associated with this TRPV1 sensitization. However, accumulating evidence suggests that, apart from pain signalling, TRPV1 subserves many other unrelated to nociception functions in the nervous system. In the brain, TRPV1 can modulate synaptic transmission via both pre- and postsynaptic mechanisms and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 123 publications
0
44
0
Order By: Relevance
“…The cooling effect can be explained as a cold hyperalgesia caused by activating TRPM8 channels and suppressing compound action potentials (CAP), raising the temperature threshold to feel coldness, i.e., making the sensation of coldness occur at a higher temperature. TRPV1 is one of the temperature-sensitive channels specific for heat stimuli (>43 • C) and extracellular pH, and it also has a crucial role in pathological forms of pain [191,192]. Activation of TRPV1 induces pain hypersensitivity (thermal hyperalgesia).…”
Section: The Receptors and Neuromodulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooling effect can be explained as a cold hyperalgesia caused by activating TRPM8 channels and suppressing compound action potentials (CAP), raising the temperature threshold to feel coldness, i.e., making the sensation of coldness occur at a higher temperature. TRPV1 is one of the temperature-sensitive channels specific for heat stimuli (>43 • C) and extracellular pH, and it also has a crucial role in pathological forms of pain [191,192]. Activation of TRPV1 induces pain hypersensitivity (thermal hyperalgesia).…”
Section: The Receptors and Neuromodulatorsmentioning
confidence: 99%
“…Activation of the GABA B receptor was found to inhibit TRPV1 sensitization, and TRPV1 activation triggers GABA release [191]. Importantly, this inhibition of TRPV1 through activation of GABA B receptors selectively suppresses the sensitized status of TRPV1 and does not affect acute TRPV1 pain signaling [191,192]. There are many plants (for example green tea (Camellia sineusis) and soybean (Glycine max)), which include GABA [194][195][196] and there are many chemical compounds in plants, which modulate the action of GABA on GABA receptors.…”
Section: The Receptors and Neuromodulatorsmentioning
confidence: 99%
“…Second, the post-administration duration required to produce the antitussive effect is shorter through inhalation than that via IP injection (5 min vs. 40 min). Third, owing to the presence of TRPV1 and EP3 receptor in a variety of organs, such as the brains (for a review, see [51,52]), inhalation of these antagonists should have less possible side effects as compared to systemic administration. In summary, our results not only reveal the higher antitussive e cacy of these antagonists via inhalation than systemic administration, but also support the interaction of TRPV1 and EP3 receptor in cough mainly occurring in airway sensory bers.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1 expression occurs in epidermis [60], polymorphonuclear granulocytes [61], smooth muscles [62], mast cells [63], dendritic cells, and macrophages [64]. Several studies have shown its expression in neuronal tissues brain regions [65,66], and in non-neuronal tissues Similarly, it is sensitized in the presence of inflammatory mediators such as prostaglandins and bradykinins, physical and chemical stimuli [67][68][69]. Capsaicin and other related compounds are lipophilic and share structural similarity with endogenous fatty acid derivatives that have been identified as TRPV1 agonists such as anandamide (an endocannabinoid) interact at intracellular regions of TRPV1 [70].…”
Section: Vasorelaxation Induced By Eugenol Involves Trpv1 Channel Actmentioning
confidence: 99%